An Online Interactive Video Vignette that Helps Students Learn Key Concepts of Fermentation and Respiration - Jean A. Cardinale (American Society for Microbiology, 2020)
Topics related to energy transformation and metabolism are important parts of an undergraduate biology curriculum, but these are also topics that students traditionally struggle with. To address this, we have created a short online Interactive Video Vignette (IVV) called To Ferment or Not to Ferment: That is the Question. This IVV is designed to help students learn important ideas related to cellular respiration and metabolism. Students in various courses across four institutions were assigned the IVV as an out-of-class preinstruction homework assignment. To test the effectiveness of this IVV on student learning, we collected and analyzed data from questions embedded in the IVV, open response reflection questions, and pre- and postassessments from IVV watchers and nonwatchers. Our analysis revealed that students who completed the IVV activity interacted productively with this online tool and made significant learning gains on important topics related to cellular respiration and metabolism. This IVV is freely available via https://www.rit.edu/cos/interactive/MINT for instructors to adopt for class use.